2013
DOI: 10.1186/1471-2407-13-225
|View full text |Cite
|
Sign up to set email alerts
|

Mortality risk of black women and white women with invasive breast cancer by hormone receptors, HER2, and p53 status

Abstract: BackgroundBlack women are more likely than white women to have an aggressive subtype of breast cancer that is associated with higher mortality and this may contribute to the observed black-white difference in mortality. However, few studies have investigated the black-white disparity in mortality risk stratified by breast cancer subtype, defined by estrogen receptor (ER), progesterone receptor (PR) and human epidermal growth factor receptor 2 (HER2) status. Furthermore, it is not known whether additional consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
28
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 56 publications
3
28
0
Order By: Relevance
“…Our study found similar racial/ethnic differences regardless of tumor characteristics (hormone receptor status and inflammatory histology). This is consistent with some previous studies, which also suggested similar racial/ethnic difference for breast cancer with various pathologic features (23, 24). These research results imply that factors other than these tumor features may play a large role in racial/ethnic disparities in breast cancer survival.…”
Section: Discussionsupporting
confidence: 93%
“…Our study found similar racial/ethnic differences regardless of tumor characteristics (hormone receptor status and inflammatory histology). This is consistent with some previous studies, which also suggested similar racial/ethnic difference for breast cancer with various pathologic features (23, 24). These research results imply that factors other than these tumor features may play a large role in racial/ethnic disparities in breast cancer survival.…”
Section: Discussionsupporting
confidence: 93%
“…In Sub-Saharan African patients a 20% frequency of ERBB2 protein expression was reported in the few published studies [Adebamowo et al, 2008;Yarney et al, 2008;Ly et al, 2012]. In a study conducted in South African patients, van Bogaert et al [2013] observed a frequency of 26% of ERBB2 overexpression, which is similar to the one observed in our cases (30.3% ERBB2 overexpression/29.7% ERBB2 copy number gain) and in line with the rates of ERBB2 protein expression reported in most of the African-American patient studies [Fregene and Newman, 2005;Adebamowo et al, 2008, Ma et al, 2013.…”
Section: Discussionsupporting
confidence: 79%
“…The general frequency of ERBB2 gains in our cases was in concordance with ERBB2 protein overexpression as evaluated by IHC. Several studies have analyzed the distribution of ERBB2 protein expression among different races, reporting contrasting findings [Joslyn, 2002;Carey et al, 2006;Adebamowo et al, 2008;Telli et al, 2011;Clarke et al, 2012;Ma et al, 2013;Adjei et al, 2014]. In Sub-Saharan African patients a 20% frequency of ERBB2 protein expression was reported in the few published studies [Adebamowo et al, 2008;Yarney et al, 2008;Ly et al, 2012].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, African-American women are more likely than white women to be diagnosed with triple-negative breast cancer, which, because of its lack of expression for the three molecular markers, does not currently have targeted treatment options (7, 15-17). A few studies have measured the contribution of molecular subtype to racial/ethnic disparities in breast cancer survival (18-20), but the findings were inconsistent when comparing survival in African-American patients with whites. One study found mortality risk difference between African-American and white women occurs only among older women diagnosed with luminal A/p53- but not with triple-negative breast cancer (18), whereas another two studies suggested higher overall mortality (19) and breast cancer specific mortality (20) in African-American than white patients with the triple-negative subtype.…”
Section: Introductionmentioning
confidence: 99%